2020
DOI: 10.1088/1361-648x/ab6140
|View full text |Cite
|
Sign up to set email alerts
|

Charge ordering in superconducting copper oxides

Abstract: Charge order has recently been identified as a leading competitor of high-temperature superconductivity in moderately doped cuprates. We provide a survey of universal and materials-specific aspects of this phenomenon, with emphasis on results obtained by scattering methods. In particular, we discuss the structure, periodicity, and stability range of the charge-ordered state, its response to various external perturbations, the influence of disorder, the coexistence and competition with superconductivity, as wel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
56
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 155 publications
(316 reference statements)
3
56
0
1
Order By: Relevance
“…5C) are all features that occur in the PDW + DSC model at the hole density where the PDW disappears. Overall, the agreement between our PDW + DSC model and the plethora of experimental characteristics is consistent with a picture in which a disordered λ = 8a 0 PDW + DSC state exists for p < pp in Bi 2 Sr 2 CaCu 2 O 8 , the λ = 4a 0 charge modulations observed by X-ray scattering (5,39) are a consequence of this state, the cuprate pseudogap coincides with the antinodal gap of the coexisting PDW, and the cuprate p ≈ p p critical point is due to disappearance of the PDW.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…5C) are all features that occur in the PDW + DSC model at the hole density where the PDW disappears. Overall, the agreement between our PDW + DSC model and the plethora of experimental characteristics is consistent with a picture in which a disordered λ = 8a 0 PDW + DSC state exists for p < pp in Bi 2 Sr 2 CaCu 2 O 8 , the λ = 4a 0 charge modulations observed by X-ray scattering (5,39) are a consequence of this state, the cuprate pseudogap coincides with the antinodal gap of the coexisting PDW, and the cuprate p ≈ p p critical point is due to disappearance of the PDW.…”
Section: Discussionsupporting
confidence: 86%
“…1 A ). Bulk probes of charge density find translational symmetry breaking in a density wave (DW) state with axial wavevectors parallel to the CuO 2 axes ( 1 , 2 , 5 ). Similarly, direct visualization with subunit-cell resolution using single-electron tunneling in Bi 2 Sr 2 CaCu 2 O 8 and Ca 2− x Na x CuO 2 Cl 2 reveals intense electronic structure modulations ( 6 , 7 ) that are locally unidirectional ( 7 , 8 ), exhibit lattice-commensurate periodicity ( 9 , 10 ) for all ( 11 ), have a d -symmetry form factor ( 8 , 12 ), and are concentrated at particle-hole symmetric energies ( 13 ) .…”
mentioning
confidence: 99%
“…A powerful experimental strategy is to monitor the response of the macroscopic and microscopic properties of interest as a function of an external control parameter [2]. In research on copper oxide high-temperature superconductors (HTS), recent experiments have indeed uncovered striking anti-parallels between the response of superconductivity measured by macroscopic transport experiments and nm-scale electronic charge correlations measured by x-ray scattering [3][4][5][6][7][8][9] to changes in temperature and magnetic field. Increasing the field, for instance, destabilizes superconductivity and enhances the amplitude and correlation length of the charge fluctuations [4,10].…”
mentioning
confidence: 99%
“…Nevertheless, as they do affect the shape of the Fermi surface via hybridization between energy bands derived from the CuO 2 planes and the CuO chains, they may thus indirectly influence the propensity of the electron system in the CuO 2 planes to CDW formation. The importance of electron-phonon interactions (EPI) for the formation of the CDW in the cuprates has been highlighted [9,26,41,[46][47][48][49], and research on classical CDW compounds has shown that its momentum dependence is also a critical parameter [50][51][52]. We argue here that the pronounced a=b anisotropies of EPI for high-energy phonons reported in YBCO [53,54] reflect the influence of the CuO chains on the EPI and play an important role in destabilizing the 3D a-CDW relative to the b-CDW.…”
mentioning
confidence: 99%
“…Copper-oxide high-T c superconductors host a variety of emerging and competing quantum phases. On the one hand, their low temperature physics is mainly characterized by unconventional d-wave superconductivity (SC); on the other hand, the normal state is actually a "strange metal" exhibiting various complex phenomena, such as pseudogap physics and charge density wave order [1][2][3][4]. Since the discovery of cuprates, the existence (or lack thereof) of well-defined quasiparticles in the normal state, as well as their temperature and doping dependence, have been the subject of intense debate.…”
Section: Introductionmentioning
confidence: 99%